Hunt a novel - Brennan, Allison (New York : Ballantine Books, 2006)
Twelve years after Miranda Moore survived the torture of a serial killer, she works as a member of a local search-and-rescue squad and has witnessed the recovery of seven of her tormentor's victims. When another student goes missing, Miranda's former lover arrives to take over the investigation, forcing her heart toward a painful choice.
Keywords: United States. -- Federal Bureau of Investigation; Serial murders; Serial murderers; Young women -- Crimes against; Romantic suspense fiction; Psychological fiction